Penguatan Pendidikan Karakter Peserta Didik Melalui Kegiatan Ekstrakurikuler Kepramukaan Di MA Muhammmadiyah Nangahure - Rahmat Rahmat; Gabriel Gleko; Abdullah Muis Kasim (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
This study aims to: (1) Describe activities in strengthening student character education through Scouting extracurricular activities at MA Muhammadiyah Nangahure (2). To find out the supporting and inhibiting factors for the implementation of extracurricular scouting activities at MA Muhammadiyah Nangahure. This study uses a qualitative approach. The data in this study were obtained through observation, in-depth interviews and documentation. The results of the study show that students at MA Muhammadiyah Nangahure have the character of discipline, religion, friendship/communicative, and responsibility. Factors that influence the application of character values ​​in scouting activities at MA Muhammadiyah Nangahure, namely: First, supporting factors, namely the implementation of the mandate of Law Number 12 of 2010 concerning the Scouting movement and the results of the 2013 Scout Movement National Conference Decision. Second, the inhibiting factor is the lack of awareness of the participants education and the influence of the social environment.